Merging Copper(I) Photoredox Catalysis and Iodine(III) Chemistry for the Oxy‐monofluoromethylation of Alkenes. (8th February 2023) - Ramkumar, Nagarajan; Baumane, Larisa; Zacs, Dzintars; Veliks, Janis
Abstract: A simple process for the oxy‐monofluoromethylation of alkenes is described. In combination with visible‐light copper(I) photoredox catalysis, an easily accessible iodine(III) reagent containing monofluoroacetoxy ligands serves as a powerful source of a monofluoromethyl (CH2 F) radical, enabling the step economical synthesis of γ ‐fluoro‐acetates from a broad range of olefinic substrates under mild conditions. Applications to late‐stage diversification of alkenes derived from complex molecules, amino acids and the synthesis of fluoromethylated heterocycles are also demonstrated. Abstract : [Bis(monofluoroacetoxy)iodo]benzene, an efficient and alternative reagent for radical monofluoromethylation under visible‐light copper(I) photoredox catalysis, provides access to CH2 F‐containing organic compounds. The broad utility of this radical monofluoromethylating reagent in alkene oxy‐monofluoromethylation reactions, including for the synthesis of fluoromethylated amino acid derivatives and heterocycles, is demonstrated.